Selective abolishment of pyrimidine nucleoside kinase activity of herpes simplex virus type 1 thymidine kinase by mutation of alanine-167 to tyrosine. - Degrève, B; Esnouf, R; De Clercq, E; Balzarini, J (2000)
Herpes simplex virus type 1 (HSV-1) encodes a thymidine kinase (TK) that markedly differs from mammalian nucleoside kinases in terms of substrate specificity. It recognizes both pyrimidine 2'-deoxynucleosides and a variety of purine nucleoside analogs. Based on a computer modeling study and in an attempt to modify this specificity, an HSV-1 TK mutant enzyme containing an alanine-to-tyrosine mutation at amino acid position 167 was constructed. Compared with wild-type HSV-1 TK, the purified mutant HSV-1 TK(A167Y) enzyme was heavily compromised in phosphorylating pyrimidine nucleosides such as (E)-5-(2-bromovinyl)-2'-deoxyuridine and the natural substrate dThd, whereas its ability to phosphorylate the purine nucleoside analogs ganciclovir (GCV) and lobucavir was only reduced approximately 2-fold. Moreover, a markedly decreased competition of natural pyrimidine nucleosides (i.e., thymidine) with purine nucleoside analogs for phosphorylation by HSV-1 TK(A167Y) was observed. Human osteosarcoma cells transduced with the wild-type HSV-1 TK gene were extremely sensitive to the cytostatic effects of antiherpetic pyrimidine [i.e., (E)-5-(2-bromovinyl)-2'-deoxyuridine] and purine (i.e., GCV) nucleoside analogs. Transduction with the HSV-1 TK(A167Y) gene sensitized the osteosarcoma cells to a variety of purine nucleoside analogs, whereas there was no measurable cytostatic activity of pyrimidine nucleoside analogs. The unique properties of the A167Y mutant HSV-1 TK may give this enzyme a therapeutic advantage in an in vivo setting due to the markedly reduced dThd competition with GCV for phosphorylation by the HSV-1 TK.